INTRODUCTION TO INDONESIAN CULTURE ABROAD THROUGH EDUCATIONAL MEDIA AT THE UGJ INTERNATIONAL KKN PROGRAM IN KAMPUNG TENGAH, KUALA PERLIS, MALAYSIA. - Siti Hidayati; Akmal Syaefulloh; Azizah Nurul Hidayah; Diffa Try Rachma; Feni Meliyani; Keyza Audya; Muhammad Hasan Mahdi; Rayhan Augusta; Widya Puteri Cahyani; Syarif Ahmad Satibi; Muhammad Ihsanudin; Lu’lu Nadhifa Huwaida; Kanya Nareswari N; Fatimah Azzahra; Dewi Sri S; Ahita Tunjung; Adinda Srimulyati (Ann Publisher, 2026)
Background. Indonesian culture as a national identity has a huge diversity. However, in the era of globalization, its existence faces serious challenges due to the dominance of foreign cultural influences, especially among the younger generation. Methods. The International Community Service Program (KKN) of Gunung Jati University (UGJ) which was held in Kampung Tengah, Kuala Perlis, Malaysia, was designed as a form of community service as well as cultural diplomacy through interactive educational media. Aims. This activity aims to increase public knowledge and understanding of Indonesian culture, foster a sense of love and pride for the nation's culture, and introduce Indonesian identity in the global arena. Cultural activities are carried out in collaboration with Universiti Utara Malaysia and the Kampung Tengah community with a participatory and educational approach. The series of activities included the introduction of Indonesian culture as a means of cross-cultural interaction. Result. The results of the activity showed that the presentation of cultural exchange received a positive response and high enthusiasm from the local community. Cross-cultural interaction has been proven to be able to strengthen social relations while increasing Malaysians' understanding of Indonesian culture. Thus, the UGJ International KKN program succeeded in introducing Indonesian culture through interactive and participatory activities. Implementation. The program was well received by the community and showed that a participatory approach can strengthen social ties and increase cross-cultural understanding between Indonesian students and Malaysian people.